A small collection of rare and new chitons (Mollusca: Polyplacophora) from the Tasmanian Museum and Art Gallery - Sirenko, Boris (Zootaxa, 2023)
A collection of rare, mainly deep-sea species of chitons collected from South Australia, Tasmania and Heard Island has been processed. In the materials there was a second find of Belknapchiton opiparus, which made it possible to significantly supplement the previous descriptions of this species. For the first time, species of genus Stenosemus have been found for Australia and Macquarie Island. Two new species (Leptochiton australis n. sp. and Belknapchiton gowlettholmesae n. sp.) have been described. A high degree of endemism of the faunas of chitons of the family Leptochitonidae of Australia and New Zealand has been confirmed.